Analisis Pengaruh Tingkat Pendidikan dan Pengangguran Terhadap Pendapatan Masyarakat di Indonesia - Zilda, Alfina Taskiyatul; Pramita, Cintaning Harda; Apriliyana, Mekar Icha; Pramana, Aurellia Bunga Ardellia; Mega, Dewani Anindita; Utami, Dewi Tri (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the impact of education level, population size, and income on the unemployment rate in Indonesia. Based on regression analysis, the results indicate that these three factors significantly influence unemployment. Education plays a crucial role in reducing unemployment, as higher education levels increase individuals' opportunities to secure suitable employment. A growing population without a corresponding increase in job creation can exacerbate unemployment. Moreover, higher income reflects an advancing economy and is associated with lower unemployment rates. To mitigate unemployment, it is recommended to improve access to quality education, provide skill training aligned with labor market demands, and implement policies that support job creation. Further research is needed to explore other factors affecting unemployment and to assess the impact of government policies in fostering inclusive and sustainable job creation.